Sensibilidade materna durante o banho - SILVA, Simone Souza da Costa (2013)
The theory of the attachment has been considering the mother-child relation as a determinant of the development. Its quality has been being related with the sensibility of the caretaker, and consequently with the quality of the relations with its own caretakers. Recently, maternal sensibility has been related with several factors such as social class and education. The goal of the present work is to investigate some variables that influence the maternal sensibility in the bath situation. Sixty baths given by mothers belonging to low or average classes were filmed. The dyads were constituted by mothers that had between 18 to 40 years and children of 0 to 1 year old. Sensitive behaviors were less frequent among mothers of low class than among mothers of middle class, which were more educated, older and which have the possibility to share the care of their infant with someone. These results suggest that the maternal sensibility is a phenomenon related to sociocultural variables.